Letter to Jane Tolmach; from George Grimes - George Grimes:::::: (1963)
Letter to Jane Tolmach from George Grimes (Chairman & Board of Trustees) sent on August 8, 1963. The letter from George Grimes displays different date and time options for Daniel Tolmach to select from to meet with Dr. Toto who will be inspecting the facility. The Dr. Toto tours must be completed before the month of December to better support the state mental hospitals in the best way possible.